Learning Support System With Computer Assisted Instruction Method - Mamed Rofendi Rofendi; Amran Manalu (SEAN Institute, 2020)
Physics is a branch of science or natural science that has an important role in advancing human thinking and thinking. Physics is the science of nature, which studies the basic elements that make up the universe, the forces acting in it, and their consequences covering a wide range from the subatomic particles that make up all matter to the behavior of the universe as a single cosmos. Science or Natural Sciences (IPA) is concerned with finding out about nature systematically, so that Science is not only the mastery of a collection of knowledge in the form of facts, concepts, or principles but also as a process of discovery. Through the high school level physical science learning application using the Computer Assisted Instruction (CAI) method, it is hoped that it can increase the user knowledge in understanding straight motion kinematics material